Role of training to reduce stress among health professionals during COVID 19: an analytical study in Meerut - Dave, Anuradha; Nasser, Kaynat; Pant, Bhawna; Dave, Sanjev (International Journal Of Community Medicine And Public Health, 2021)
Background: A healthy job is likely to be one where the pressures on employees are appropriate in relation to their abilities and resources, to the amount of control they have over their work, and to support they receive from people who matter to them. Experiencing an infectious disease outbreak can cause fear, anxiety and stress. Methods: A cross sectional study was conducted in Subharti Medical College, Swami Vivekanand Subharti University, Meerut in the month of September 2020–October 2020 on 127 health care professional (69 doctors and 58 nurses) who were interviewed randomly working in the level III COVID hospital using professional stress score by David Fontanna. Results: Training received by the doctor and nurses during COVID-19 pandemic for infection prevention was more significantly associated with mild professional stress (p<0.00) than moderate professional stress (p<0.027). Conclusions: Training showed positive impact by enhancing their confidence level to manage stress during pandemic situation.